Portugal : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Portugal has made notable progress over the past year in reducing uncertainty over near-term risks. The exit from the Excessive Deficit Procedure in 2017, together with a marked improvement in stability and confidence in the banking system, have helped bolster investor confidence and contributed to a sharp narrowing in sovereign debt spreads since mid-March. The near-term growth outlook has also improved considerably as the ongoing recovery continues to gain momentum, with a pickup in exports and investment alongside the continued growth in private consumption. Tourism remains a key driver of growth, but has also been accompanied by a broad-based pickup in exports of goods in recent quarters.